The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/10874200802143998
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Neurotherapy on College Students' Cognitive Abilities and Emotions

Abstract: Background. In past research, several case studies and five controlled-group studies explored the effect of electroencephalographic (EEG) biofeedback on intelligence, attention, and behavior in children diagnosed with attention deficit hyperactivity disorder, but no studies have explored the effects of EEG biofeedback in nonclinical adults on measures of response control, mood, emotional intelligence, and self-efficacy.Method. Sixteen nonclinical college students were randomly assigned to receive Beta=Sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Neurofeedback also has documented results for cognitive and memory enhancement in normal individuals (Angelakis et al, 2007;Boulay, Sarnacki, Wolpaw, & McFarland, 2011;Egner, Strawson, & Gruzelier, 2002;Fritson, Wadkins, Gerdes, & Hof, 2007;Gruzelier, Egner, & Vernon, 2006;Hanslmayer, Sauseng, Doppelmayr, Schabus, & Klimesch, 2005;Hoedlmoser et al, 2008;Keizer, Verment, & Hommel, 2010;Rasey, Lubar, McIntyre, Zoffuto & Abbott, 1996;Vernon et al, 2003;Zoefel, Huster, & Herrmann, 2010). Neurofeedback to enhance cognitive functioning and to counter the effects of aging has been referred to as ''brain brightening'' (Budzynski, 1996).…”
Section: Cognitive and Memory Enhancementmentioning
confidence: 99%
“…Neurofeedback also has documented results for cognitive and memory enhancement in normal individuals (Angelakis et al, 2007;Boulay, Sarnacki, Wolpaw, & McFarland, 2011;Egner, Strawson, & Gruzelier, 2002;Fritson, Wadkins, Gerdes, & Hof, 2007;Gruzelier, Egner, & Vernon, 2006;Hanslmayer, Sauseng, Doppelmayr, Schabus, & Klimesch, 2005;Hoedlmoser et al, 2008;Keizer, Verment, & Hommel, 2010;Rasey, Lubar, McIntyre, Zoffuto & Abbott, 1996;Vernon et al, 2003;Zoefel, Huster, & Herrmann, 2010). Neurofeedback to enhance cognitive functioning and to counter the effects of aging has been referred to as ''brain brightening'' (Budzynski, 1996).…”
Section: Cognitive and Memory Enhancementmentioning
confidence: 99%
“…Low beta NFB training was associated with faster reaction times and increased target P300 amplitudes, whereas no changes were evident in the control group (Egner and Gruzelier 2004). Nevertheless, Fritson et al (2008) did not find beneficial effects in attention of a simultaneous SMR NFB training and theta/high beta inhibition. They found a significant posttraining change in the experimental group regarding response control but no significant changes in attention for either the control or treatment group.…”
Section: Mixed Trainingmentioning
confidence: 67%
“…Beta augment NFB training can be used to enhance attentional processing . And more recent research has shown that SMR augment training can enhance attentional (Doppelmayer and Weber 2011;Gruzelier 2001, 2004;Fritson et al 2008) and declarative memory performance (Hoedlmoser et al 2008), facilitate semantic processing in a working memory task and familiarity-based processes in working memory (Guez et al 2015), improve surgical technique while considerably reducing time on task , and reduce sensorimotor interference . Finally, augment gamma NFB training was positively correlated with a decrease of selectively retrieving binding costs and an increase in intelligence score (Keizer et al 2010a, b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seans sayıları ise yine spor bilimleri alanında uygulanan protokollere bağlı olmakla birlikte en az 10-15 seans arasındadır. Ancak Fritson ve arkadaşları sağlıklı bireylerde NGB antrenmanının etkisinden söz edilebilmesi için en az 20 seanslık NGB antrenmanının uygulanması gerektiğini bildirmişlerdir [37].…”
Section: Nöro-geribildirim Antrenman Sayısı Ve Süresiunclassified